Chitosan poly (acrylic acid) semiIPN patch for drug encapsulation and release - Gonzales, Christian; Leal, Mari Kaira O.; Andalis, Ivy Marie C.; Chua, Modesto T.; Chakraborty, Soma (2011)
In recent years, the formulation of transdermal delivery patches using biopolymers has been given extensive attention. Chitosan, a derivative of chitin, has the ability to form strong films, hence forms a prime component of wound dressing patch. The research reports the fabrication of semi-interpenetrating network (semi-IPN) hydrogel patch from Chitosan (Ch) and polyacrylic acid (PAA). PAA is a biocompatible, biodegradable, and bioadhesive and can absorb a large amount of water. Semi-IPN composed of PAA with Ch and Glycidyl Trimethyl Ammonium Chloride (Quat 188) modified Ch was synthesized by polymerizing AA and crosslinking it with N,N' methylene biscarylamide in the presence of unmodified and modified Ch in deionized water at 70°C using potassium persulfate as the initiator. Ch was modified to improve its antimicrobial property. The strength of the semi-IPNs improved with increase of the crosslink density, molecular weight of Ch and Ch to PAA ratio and by Quat 188 modification. Unmodified Ch semi-IPN swelled 400% in pH 7 and 325% in pH 5.5 buffer in 2h. In 2h Quat 188 modified Ch semi-IN swelled 1200% and 1000& in pH 5.5 and 7 buffer, respectively. Two drugs AgNO3 and mafenide acetate (MFC) were encapsulated in the semi-IPNs. The semi-IPNs could incorporate 100% of free AgNO3 in 10 minutes from its aqueous solution but showed negligible release. In case of MFC, pH dependent encapsulation and release was observed. Modified Ch semi-IPN encapsulated 95% MFC from its solution in 2h and release 56% MFC in 10h at pH 5.5 whereas unmodified chitosan semi-IPN encapsulated 86% MFC from its solution in 6h and release 35% MFc in 10h at pH 7.
Keywords: Chitosan